Book Reviews (Historia, 2021)
1.Dagboek van Adam Tas2. Kariel, Henry, S. (Red.) The Political Order: A Reader in Political Science3. Naude, J. D.: Genl. J. B. M. Hertzog en die Onstaan van die Nasionale Party